O currículo escolar e as suas possibilidades em relação à superação do racismo - Ferrari, Alice Rosa de Sena (2021)
This Doctoral dissertation is part of the discussions proposed by the Education and Research Group on Curricular Justice (Grupo de Educação e Pesquisa em Justiça Curricular - GEPEJUC), led by PhD Professor Branca Jurema Ponce, focusing on the principles of the Curricular Justice and its dimensions: knowledge, care and coexistence. The object of research is the relationship between the school curriculum and the overcoming of racism. Racism is understood as a social construction that structurally affects the life of the black population, including through the school curriculum, so it is necessary to overcome it. As a hypothesis, it is defined that Education for ethnic-racial relations, as provided by Law no. 10,639/2003, reedited by Law no. 11,645/2008, is a public policy that allows the recognition, confrontation and overcoming of racism. It is admitted that Education for ethnic-racial relations is materialized in the school curriculum under the aegis of knowledge, care and coexistence (dimensions of Curricular Justice), from the collective construction of curricula, the political formation of subjects, the acceptance of diversities, the promotion of intercultural dialogue, the proposition of black representation, enabling the strengthening of black identity. The general objective of this Doctoral dissertation is to build knowledge about the school curriculum, identifying emphases and challenges in relation to the recognition, confrontation and overcoming of racism as racial prejudice and discrimination. The specific objectives are: a) to conduct exploratory research to approach the object of study through: Systematic Literature Review (SLR) in academic research on racism in the school curriculum, interviews and questionnaires; b) to identify curricular practices for recognizing, confronting and overcoming racism in the context of public schools through: observations, interviews and document analysis. The insertion in a public school in the city of São Paulo, Brazil, occurred through the observation of curricular practices; interview with school management, pedagogical coordination and teachers; and analysis of the Pedagogical Master Plan of the school unit. The research presents a qualitative approach, according to Chizzotti (2014), from bibliographic and documentary basis. The research instruments are based on Gil (2008), Brandão (2003) and Severino (2007). The collected data were approached in line with the content analysis proposed by Bardin (2016). The theoretical contribution is formed by: Apple (2000, 2006, 2017), Apple and Beane (2001), Torres Santomé (1995, 1997, 2011, 2013), Ponce (2006, 2016, 2018), Ponce and Araújo (2019), Ponce and Neri (2015, 2017) and Neri (2018), about the school curriculum; Munanga (1986, 1994, 2004, 2005a, 2005b, 2008, 2010, 2013, 2014, 2015), who contributes to the reflection on racism and its manifestations; Gomes (2003, 2005a, 2005b, 2008, 2010a, 2010b, 2011a, 2011b, 2012a, 2012b, 2019a, 2019b) and Silva (2005, 2007, 2012, 2018), who present elements about an education for ethnic-racial relations. The main results of this Thesis contributed to the construction of knowledge about education for ethnic-racial relations as a possibility of recognizing, confronting and overcoming racism through the school curriculum